Spatial Vulnerability in Weavers Settlement in India: A Bibliometric Study - Nupur, Ar.; Mathur, Mayank; Gupta, Ruchita (Journal of Data Science, Informetrics, and Citation Studies)
Handloom weaving is a time-honored tradition in India. Once, all textile production relied solely on handlooms, but today it faces stiff competition from power looms in domestic and global markets. The Government of India, through various initiatives and programs under the Ministry of MSME and the Made in India campaign, is focusing on modernising the handloom sector and supporting weavers. They recognise the importance of promoting handloom at both national and international levels to maintain its market presence, given its unique, inimitable identity as a craft passed down through generations. This labour-intensive industry can contribute to achieving the Sustainable Development Goals and the 169 targets set by the United Nations. Studies from international journals, the International Labour Organisation, handloom census reports, and national journals reveal that handloom weaving workers are home-based workers, as noted in the fourth handloom census. This craft is a family tradition, typically practiced within homes. Weavers require more space than other home-based workers due to the need to set up looms. Women, part of the informal labour sector, also play a role in handloom production by preparing threads for weaving, often using kitchen space and thus compromising cooking areas. Researchers have not sufficiently addressed the spatial challenges faced by weavers, as the minimum area recommended by various government schemes does not accurately reflect their needs. As a result, they often have to manage with limited living and kitchen space. Weavers also face respiratory issues due to thread particles and inadequate ventilation within congested settlements, leading to PM2.5 and PM10 exposure. Overcrowding and lack of ventilation, especially in unplanned settlements of weavers, make them more vulnerable and bear the largest exposure burden to indoor air pollution. In urban areas, traffic congestion can occur when threads are straightened on roads, or children's play areas are restricted when this is done in parks, causing social vulnerability for children and traffic problems. Rural handloom weavers may be more disadvantaged than their urban counterparts in accessing raw materials and marketing their products. So, there is a need to have the spatial aspect as one of the parameters to study the vulnerability of handloom weavers, other than economic factors that impact the social, health, and environmental aspects.
Keywords: Handloom Weaving; Home-Based Workers; Household Weavers; Spatial Vulnerability; Vulnerability Assessment; Bibliometrics; India.